Effect of Mung Bean Sprout (Vigna radiata (L)) Extract on Physical Stress-Induced Atherosclerosis of Male Wistar Rat - Azham Purwandhono; Rena Normasari (Journal of Agromedicine and Medical Sciences, 2015)
Coronary heart disease is an important health problem. It is estimated that the death rate from coronary heart disease by 23,4 millions in 20130 (WHO, 2009). Excessive physical activity can cause oxidative stress which lead to atherosclerosis. Mung bean sprouts (Vigna radiata (L)) contain vitamin E, vitamin C, fenol, flavonoid, fitosterol, and other minerals. The aim of this study is to determine the effect of mung beans sprout extract on on the thicknes of the tunica intima-media on physical stress-induced atherosclerosis of male wistar rat. This research is true experimental study using 20 male wistar rat were divided into five groups: negative control, positive control and treatment groups P1, P2, P3 (physical stress + bean sprout extract 50 mg/day, 100 mg/day, 200 mg/day for 10 days). There is significant decrease of MDA serum level in the treatment groups.Keywords : Vigna radiata, physical stress, thicknes of tunica intima-media